PENGARUH PEMBANGUNAN INFRASTRUKTUR TERHADAP INVESTASI DI KABUPATEN GORONTALO - Abd Latif (Prodi Ekonomi Syariah Pascasarjana IAIN Sultan Amai Gorontalo, 2022)
This study aims to determine the magnitude of the influence of infrastructure development in the field of Education, Infrastructure in the Health sector and Infrastructure in the Agriculture sector on increasing investment in the form of PMA and PMDN in Gorontalo Regency. The results of secondary data processing using multiple regression analysis where the infrastructure of Education, Health, and Agriculture simultaneously showed a significant effect where the F-count 25.848 was greater than the F-table 3.47. While partially; infrastructure in education and agriculture shows the most significant effect compared to health infrastructure as evidenced by t-test analysis, where t-count X1 = 4.743 and X2 = 7.618 is greater than t-table 1.714. Overall, the three variables show a positive and quite strong influence on increasing investment in Gorontalo Regency, this can be proven by looking at the correlation coefficient (R) of 0.895 or 89% which increases in the three independent variables will result in an increase in the dependent variable, namely investation. The implications of this research are directed at the expectations of the local government of Gorontalo Regency in making public policies regarding the acceleration of infrastructure development and making a number of breakthroughs or innovations that are effective in attracting investors to invest in the regional infrastructure development sub-sector.